2017
DOI: 10.1080/10717544.2017.1402219
|View full text |Cite
|
Sign up to set email alerts
|

Development of magnetic anionic liposome/atelocollagen complexes for efficient magnetic drug targeting

Abstract: Magnetic nanoparticle-incorporated liposomes (magnetic liposomes) are considered a promising site-specific drug delivery carrier vehicle. With regard to their surface charge, magnetic anionic liposomes (Mag-AL) demonstrate little toxicity in comparison with magnetic cationic liposomes (Mag-CL), whereas their cellular association and uptake efficiency are low. In the current study, we constructed complexes of Mag-AL and atelocollagen (ATCOL), which is a biocompatible and minimally immunogenic biomaterial, to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Versions of the liposomal nanoparticles exist. These include magnetic nanoparticles [ 67 ]; thermosensitive liposome-in-gel [ 5 ]; transferrin receptor (TR)-targeted liposomal cisplatin [ 68 ]; magnetic thermosensitive cationic liposomes [ 69 ] and so on. Novel technologies have also been reported [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Versions of the liposomal nanoparticles exist. These include magnetic nanoparticles [ 67 ]; thermosensitive liposome-in-gel [ 5 ]; transferrin receptor (TR)-targeted liposomal cisplatin [ 68 ]; magnetic thermosensitive cationic liposomes [ 69 ] and so on. Novel technologies have also been reported [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with magnetic cationic liposome (MCL), MAL showed both concentration-and time-dependent cellular uptake without any cytotoxic effects in vitro on RAW264 cells. However, the use of atelocollagen at concentrations (more than 20 μg/mL) will form aggregates at 37 C and inhibit cellular uptake due to large particle size [93].…”
Section: Collagenmentioning
confidence: 99%
“…coated MLs with atelocollagen to improve cellular uptake efficiency. After intravenous injection of atelocollagen-coated MLs, a disc-shaped magnet was placed close to the liver to accelerate ML enrichment inside the liver (Kono et al., 2017 ). Another study showed that magnetic anionic liposome (Mag-AL) binding was significantly increased under magnetic guidance in RAW264 cells (a murine macrophage-like cell line) compared to that of the control group.…”
Section: Comparison With Other Nanomaterialsmentioning
confidence: 99%